Influence of the environmental heterogeneity of breeding ponds on anuran assemblages from southeastern Brazil - Vasconcelos, T. S. [UNESP]; Santos, T. G. [UNESP]; Rossa-Feres, D. C. [UNESP]; Haddad, Celio Fernando Baptista [UNESP] (Natl Research Council Canada-n R C Research Press, 2009)
We hypothesized that the environmental heterogeneity of breeding ponds influences the species composition and species richness of anuran assemblages from southeastern Brazil, because it provides humidity, shelter, and breeding microhabitats for anuran species, which can result in an increasing number of species in a given habitat. To begin, we tested whether the occurrence of anuran species in each breeding pond is different from a null model of random placement of species in those ponds. We then performed two tests to evaluate which of the five environmental descriptors of breeding ponds influence (1) the species composition and (2) species richness. Species composition of the 38 breeding ponds was correlated with number of edge types, number of plant types along the edges of the breeding ponds, and the hydroperiod. Neither the percentage of vegetation cover on the water's surface nor the size of the breeding ponds were correlated with species composition. Only the number of edge types was correlated with species richness of breeding ponds. The correlation of three environmental descriptors with species composition and one environmental descriptor with species richness, as well as the high beta diversity among breeding ponds, suggest that the analyses of environmental heterogeneity on species composition was more informative than was the analysis for species richness, because breeding ponds with similar species richness can have distinct species composition among them (high beta diversity).